A parents' interpersonal communication in mentoring at gadgets used for elementary school children - Yunita Sari; Mulan Jameela; Chika Laily; Hasna Nabilah (Jurnal Mantik, 2023)
This article aims to explain about interpersonal communication carried out by parents in assisting the use of gadgets for their children who are still in elementary school.  Using the constructivism paradigm, the case study method with data collection techniques through interviews with internal informants of Indonesian Child Protection Commission (KPAI), namely one of the supervisory analysts and institutional relations in the family sub-cluster, Alternative Care, DKI Jakarta Provincial Education Office, elementary school teachers and parents who have children still in elementary school. The results showed that it is very important to carry out interpersonal communication of parents through assistance in the use of gadgets for their children to avoid negative impacts on content that is not suitable for elementary school children.  The importance of quality time between parents and children is interpersonal communication, by doing activities together, without gadgets, and both parents must be committed.